Answer :



Using the splitting middle term - the middle term of the general equation is divided in two such values that:


Product = a.c


For the given equation a = 1; b = -18; c = 77


= 1.77 = 77


And either of their sum or difference = b


= - 18


Thus the two terms are - 7 and - 11


Sum = - 7 - 11 = - 18


Product = - 7. - 11 = 77




x(x-7)-11(x-7) = 0


(x-7)(x-11) = 0


(x-7) = 0 or (x-11) = 0


x = 7 or x = 11


Roots of equation are 7, 11


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Which of the follRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics

Solve each of theRS Aggarwal - Mathematics